Особливості репродуктивної фенології представників роду Frailea Britton et Rose (Cactaceae Juss.) в умовах культури - Niepiein, A.Yu. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The results of observations of the several factors influenced on the flowering phenology and some ontogenesis stages of the genus Frailea Britton et Rose (Cactaceae Juss.) under glasshouse conditions are presented. The influence of age and morphometric characteristics of the generative period beginning and flowering duration season is determined.